2018
DOI: 10.5114/jogi.2018.73387
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided surgical suction evacuation (US-SSE) for missed miscarriage

Abstract: Introduction: Surgical evacuation of the uterine contents in first trimester missed miscarriage is a blind procedure, carrying a risk of complications. This study was designed to evaluate the outcome of the implemented protocol of ultrasound-guided surgical suction evacuation (US-SSE) for first trimester missed miscarriage. Material and methods: Two hundred and twenty women diagnosed with missed miscarriage in the first trimester of pregnancy were included in this study and classified in two groups: 124 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Similarly, some patients qualified for the IVF procedure using the donor's egg cells were given pregnancies before the procedure of in vitro fertilization began. It has been found that the administration of DHEA in patients with premature ovarian failure prolongs the chances of pregnancy, reduces the risk of miscarriage and increases the chance of success when using IVF methods [14,15,16,[54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some patients qualified for the IVF procedure using the donor's egg cells were given pregnancies before the procedure of in vitro fertilization began. It has been found that the administration of DHEA in patients with premature ovarian failure prolongs the chances of pregnancy, reduces the risk of miscarriage and increases the chance of success when using IVF methods [14,15,16,[54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized control trial by Acharya et al (11), complications of abortion were significantly reduced under ultrasound-guidance (<4%) in comparison to without ultrasound guidance (>15%). Another related randomized control trial showed that the incidence of uterine perforation was 0% with ultrasound guidance and approximately 3% without ultrasound guidance (12). While some may argue that routine ultrasound-guidance for surgical abortions may not be practicable from the economic standpoint in developing countries, it is worth noting that the annual cost of treating major complications of abortion in developing countries is over 500 million US dollars (13), including 200 million dollars on post-abortion care (14).…”
Section: Discussionmentioning
confidence: 99%